2021
DOI: 10.1101/2021.03.26.21254416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring Integrated Environmental Viral Surveillance of Indoor Environments: A comparison of surface and bioaerosol environmental sampling in hospital rooms with COVID-19 patients

Abstract: The outbreak of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has dramatically transformed policies and practices surrounding public health. One such shift is the expanded emphasis on environmental surveillance for pathogens. Environmental surveillance methods have primarily relied upon wastewater and indoor surface testing, and despite substantial evidence that SARS-CoV-2 commonly travels through space in aerosols, there has been limited indoor air surveillance. This study investigated the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 69 publications
(81 reference statements)
0
14
0
Order By: Relevance
“…There is a paucity of clinical studies of air sampling for SARS-CoV-2 detection: for example, one recent preprint comparing a commercial air sampler (not TGA listed) to other environmental testing in 32 hospital rooms of COVID-19 positive patients found that among positive rooms, 32% had only active air samples that returned positive results, while ∼27% and ∼9% had only one or more surface swabs or passive settling plates that returned a positive result respectively; 32% of rooms had more than one sample type that returned a positive result. 99 Therefore, the utility of air sampling in various prevalence contexts relevant to Australia requires further research. 99 …”
Section: Other Novel Emerging Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a paucity of clinical studies of air sampling for SARS-CoV-2 detection: for example, one recent preprint comparing a commercial air sampler (not TGA listed) to other environmental testing in 32 hospital rooms of COVID-19 positive patients found that among positive rooms, 32% had only active air samples that returned positive results, while ∼27% and ∼9% had only one or more surface swabs or passive settling plates that returned a positive result respectively; 32% of rooms had more than one sample type that returned a positive result. 99 Therefore, the utility of air sampling in various prevalence contexts relevant to Australia requires further research. 99 …”
Section: Other Novel Emerging Technologiesmentioning
confidence: 99%
“… 99 Therefore, the utility of air sampling in various prevalence contexts relevant to Australia requires further research. 99 …”
Section: Other Novel Emerging Technologiesmentioning
confidence: 99%
“…Several studies have shown the utility of active air samplers to detect aerosols containing SARS-CoV-2 [38][39][40][41][42][43] in controlled settings and locations with known SARS-CoV-2 cases. Horve et al (2021) demonstrated consistent detection of heat-inactivated SARS-CoV-2 virus at an aerosol concentration of 0.089 genome copies per liter of air (gc/L) when air samples were collected in a room-scale experiment during an eight-hour interval 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Horve et al (2021) demonstrated consistent detection of heat-inactivated SARS-CoV-2 virus at an aerosol concentration of 0.089 genome copies per liter of air (gc/L) when air samples were collected in a room-scale experiment during an eight-hour interval 38 . Another study compared the effectiveness of surface and bioaerosol sampling methods to detect SARS-CoV-2 and showed active air samples detected SARS-CoV-2 in 53% of the samples when run for 1-2 hours in hospital rooms of COVID-19 patients, while passive air sampling and surface swabs detected SARS-CoV-2 in only 12% and 14% of samples, respectively 39 Increases in patient viral load were associated with lower cycle threshold (Ct) values detected in near (1.2 meters) and far (3.5 meters) air samplers 40 . Lastly, a study demonstrated the utility of using active air samplers to track the presence and concentration of virus in air longitudinally during COVID-19 isolation periods in student dormitories.…”
Section: Introductionmentioning
confidence: 99%
“…Renninger et al emphasize the need for surveillance testing, especially when affected individuals are asymptomatic, and successfully use dust as a tool for COVID-19 surveillance [ 12 ]. In another study, air in a hospital room was sampled at 200 L per minute using an AerosolSense air sampler to efficiently detect SARS-CoV-2 present in the air [ 13 ]. However, most of these surveillance techniques are based on reverse transcription polymerase chain reaction (RT-PCR), which, although effective, is time consuming, expensive, and not suitable for providing real-time alerts.…”
Section: Introductionmentioning
confidence: 99%